Combating Drug-Resistant Bacteria Using Photothermally Active Nanomaterials: A Perspective Review - Kaur, Kawaljeet; Reddy, Sagar; Barathe, Pramod; Shriram, Varsha; Anand, Uttpal; Proćków, Jarosław; Kumar, Vinay (Frontiers in Microbiology, 2021)
Injudicious use of antibiotics has been the main driver of severe bacterial non-susceptibility to commonly available antibiotics (known as drug resistance or antimicrobial resistance), a global threat to human health and healthcare. There is an increase in the incidence and levels of resistance to antibacterial drugs not only in nosocomial settings but also in community ones. The drying pipeline of new and effective antibiotics has further worsened the situation and is leading to a potentially “post-antibiotic era.” This requires novel and effective therapies and therapeutic agents for combating drug-resistant pathogenic microbes. Nanomaterials are emerging as potent antimicrobial agents with both bactericidal and potentiating effects reported against drug-resistant microbes. Among them, the photothermally active nanomaterials (PANs) are gaining attention for their broad-spectrum antibacterial potencies driven mainly by the photothermal effect, which is characterized by the conversion of absorbed photon energy into heat energy by the PANs. The current review capitalizes on the importance of using PANs as an effective approach for overcoming bacterial resistance to drugs. Various PANs leveraging broad-spectrum therapeutic antibacterial (both bactericidal and synergistic) potentials against drug-resistant pathogens have been discussed. The review also provides deeper mechanistic insights into the mechanisms of the action of PANs against a variety of drug-resistant pathogens with a critical evaluation of efflux pumps, cell membrane permeability, biofilm, and quorum sensing inhibition. We also discuss the use of PANs as drug carriers. This review also discusses possible cytotoxicities related to the therapeutic use of PANs and effective strategies to overcome this. Recent developments, success stories, challenges, and prospects are also presented.